2013
DOI: 10.1111/ahg.12048
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Necrosis Factor and Interleukin‐6 Gene Polymorphisms and Endometriosis Risk in Asians: A Systematic Review and Meta‐Analysis

Abstract: Summary A relationship between endometriosis and tumor necrosis factor (TNF‐α) and interleukin‐6 (IL‐6) gene polymorphisms has been raised for Asians. However, this topic is controversial. This study was a meta‐analysis to explore whether TNF‐α/IL‐6 gene polymorphisms were associated with a risk of endometriosis in Asians. By searching PubMed, HuGENet, and China National Knowledge Infrastructure (CNKI) databases, 17 studies were identified and included (3372 cases and 4008 controls). The odds ratio (OR) with 9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 43 publications
1
12
0
1
Order By: Relevance
“…Increases in cytokine levels in body fluids, such as peritoneal fluid and presence of cytokine expressions in endometrial cells, give rise to the thought that there is an interaction between these cases and they can be related to pathogenesis and the spread of the disease. Earlier studies have shown the existence of TNF-α and IL-6 in body fluids of patients with endometriosis 5,17,21,22 . In our study, this is the first time that both TNF-α and IL-6 expressions have been shown immunohistochemically in both normal and ectopic endometrial tissue.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Increases in cytokine levels in body fluids, such as peritoneal fluid and presence of cytokine expressions in endometrial cells, give rise to the thought that there is an interaction between these cases and they can be related to pathogenesis and the spread of the disease. Earlier studies have shown the existence of TNF-α and IL-6 in body fluids of patients with endometriosis 5,17,21,22 . In our study, this is the first time that both TNF-α and IL-6 expressions have been shown immunohistochemically in both normal and ectopic endometrial tissue.…”
Section: Discussionmentioning
confidence: 96%
“…It is widely accepted that the pathogenesis of the disease is related to the accumulation of cytokines and various growth factors secreted from macrophages and leukocytes in the peritoneal fluid 8,18 . Undeniably, it is found that, many cytokines and growth factors, such as TNF-α 5,21,22 , IL-1 23 , IL-6 17 , IL-8 24,25 , IL-10 26 , VEGF 16 , MCP-1 25 and MCP-2 increased significantly in peritoneal fluid of women with endometriosis compared to healthy women. It is thought that the presence of a high percentage of peritoneal fluid may have a role in triggering the development of endometriosis; however, the presence of various cytokines and increased levels of these cytokines in body fluids have been shown in several recent studies 5,17,23,25 .…”
Section: Discussionmentioning
confidence: 99%
“…Interleukin-6 IL-6 -174C/G gene polymorphisms may be a risk factor for endometriosis for Asians (125). IL-6 -634C/G and ICAM-1 469K/E polymorphisms synergistically affect the susceptibility for endometriosis in the Japanese population (126).…”
Section: Il-6mentioning
confidence: 99%
“…long cytoplasmic tail, 1 (142). TNF-α -238A/G gene polymorphisms may be a risk factor for endometriosis for Asians (125). TNFA promoter polymorphism was associated with susceptibility to endometriosis (144).…”
Section: Kir3ds1mentioning
confidence: 99%
“… 4 , 5 Even though several meaningful conclusions have been drawn in previous studies, 6 8 the exact etiology of endometriosis remains unclear and standard treatment for endometriosis has been deficient so far. 9 To sum up, considering the unfavorable outcomes of people who are affected by endometriosis and vague etiology of endometriosis-related infertility, it is of great significance to further explore genetic risk factors associated with endometriosis-related infertility.…”
Section: Introductionmentioning
confidence: 99%